Electrical Power Systems - Husain, Ashfaq (New Delhi : CBS Publishers, 2007)
Engineering
Keywords: Electrical; Power; Power Systems; Electrical Power; Supply Systems; Conductors; Power Cables; Line Parameters; Long Transmission Lines; Network Constants; Power Circle Diagrams; Symmetrical Faults; Symmetrical Components; Power Stability; Over Voltage Protection; Neutral Grounding; Power Factor Improvement; Voltage Stability; Transmission Systems